Wireless broadband in a box. - Schrick, B. (IEEE spectrum)
Despite all the talk about broadband, only about 7%, or 7.5 million, of US households subscribed to high-speed Internet access services as of last June, according to a February report issued by the US Federal Communications Commission (FCC). The situation is not much different elsewhere; only a few countries with much smaller populations report somewhat higher percentages. Lack of need is, one reason for the unimpressive numbers. Another reason is difficulty in getting service. For a variety of reasons, many would-be subscribers have been unable to get cable or digital subscriber line (DSL) service. For them, a fairly new type of technology known as non-line-of-sight (NLOS) wireless may be just what they need. NLOS wireless systems offer high-speed Internet access over several kilometers without directional antennas. When wireless routers are mounted on a subscribers' building, they can configure themselves into a mesh network. Mesh networks solve the problem of connecting widely separated wireless routers that cannot see each other by using many intermediate points, each of which can be seen by its neighbors. The article looks at the potential of this technology.